Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.20517/2394-4722.2017.34
|View full text |Cite
|
Sign up to set email alerts
|

Tumor heterogeneity and therapy resistance - implications for future treatments of prostate cancer

Abstract: Aim:To develop new therapies for prostate cancer, disease heterogeneity must be addressed. This includes patient variation, multi-focal disease, cellular heterogeneity, genomic changes and epigenetic modification. This requires more representative models to be used in more innovative ways. Methods: This study used a panel of cell lines and primary prostate epithelial cell cultures derived from patient tissue. Several assays were used; alamar blue, colony forming assays, γH2AX and Ki67 immunofluorescence and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 44 publications
(56 reference statements)
0
18
0
Order By: Relevance
“…Our previous studies using this technique showed that prostate cell lines and primary prostate epithelial cells differ in their size, speed and growth rates. We also showed that the transit amplifying cells (TA) and committed basal cells (CB) found within primary cultures have different cell signatures, with the TA cells being smaller, thicker and faster than the CB cells (27).…”
Section: Using Primary Prostate Epithelial Cells As a Cell Modelmentioning
confidence: 85%
See 1 more Smart Citation
“…Our previous studies using this technique showed that prostate cell lines and primary prostate epithelial cells differ in their size, speed and growth rates. We also showed that the transit amplifying cells (TA) and committed basal cells (CB) found within primary cultures have different cell signatures, with the TA cells being smaller, thicker and faster than the CB cells (27).…”
Section: Using Primary Prostate Epithelial Cells As a Cell Modelmentioning
confidence: 85%
“…Prostate cancer is a multifocal disease so there may be more than one tumour in each patient (26) and there is inter-patient variability. Along with this there is cellular heterogeneity within each tumour, multiple gene mutations, gene fusions and epigenetic changes (27). Finding a cellular model(s) to address all of these parameters is challenging.…”
Section: Addressing Prostate Cancer Heterogeneitymentioning
confidence: 99%
“…Pre-treatment of the SC population with a low (non-cytotoxic) dose of Trichostatin A (TSA), a histone deacetylase (HDAC) inhibitor, increased the radio-sensitivity of the SC fraction by 20%–40%, whilst not affecting the more differentiated and radio-sensitive cells. A significant synergy with radiation after treatment with another (clinically approved) HDAC inhibitor, Vorinostat (suberanilohydroxamic acid—SAHA) was observed in multiple primary prostate epithelial cultures [102] as defined by colony forming ability.…”
Section: Increased Heterochromatin and Rapid Chromatin Condensatimentioning
confidence: 99%
“…Prostate cancer is a biologically heterogeneous disease and its complex nature provides a significant challenge for its clinical management. The nature of prostate cancer heterogeneity is characterised by interpatient, intertumoural (multifocal disease), intratumoural, genomic and epigenetic heterogeneity, which raises considerable challenges when developing therapies [17]. Nevertheless, several genomic landscape studies of primary and metastatic prostate cancer have identified distinct molecular subtypes and potentially actionable genomic driver events [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%